Modeling of semiconducting piezoelectric nanowires for mechanical energy harvesting and mechanical sensing. (May 2015) - Tao, R.; Ardila, G.; Montès, L.; Mouis, M.
Abstract: ZnO and GaN semiconducting piezoelectric nanowires (NWs) have attracted much attention because of their improved mechanical and piezoelectric properties compared to bulk materials. They have been integrated into different devices ranging from sensors to energy harvesting devices. In this review article we focalize on the modeling of these nanostructures and devices: First, we synthesize the modeling studies at an individual level including the different approaches developed. Then we consider NW arrays integrated into devices for mechanical energy harvesting applications and the different modeling techniques, including finite element methods, analytical methods and equivalent circuit models, to estimate the performance and the optimization guidelines of such devices. Finally, composite materials integrating piezoelectric NWs and a dielectric matrix are also considered as a route for improved performance compared to piezoelectric thin films. Graphical abstract: Highlights: Modeling of individual semiconducting piezoelectric nanowires is reviewed. Optimization guidelines of nanogenerators and mechanical sensors are discussed. Models show that composite piezo nanomaterials could outperform thin piezo films. Challenges on the modeling of piezo nanowires and devices are presented.